Religious literacy for strengthening identity and solidarity of the Cham Muslim Community in Cambodia - Rahmi, Lailatur; Nelmawarni, Nelmawarni; Sandora, Lisna; Alfi, Math; Hutagalung, Mawaddah Warahma (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: The Cham Muslim community in Roka Po Pram, Cambodia, faces structural barriers in preserving their religious identity due to the dominance of Theravada Buddhism, lack of qualified teachers, and inadequate religious education infrastructure. Purpose: This study aims to enhance religious literacy and reinforce the community’s cultural and social identity through a participatory model. Method: A Community-Based Research (CBR) approach was applied in four stages: foundation, planning, data collection, and action. Data were collected through interviews, focus group discussions, and participatory observations involving teachers, parents, youth, and local leaders. Findings: The results revealed increased community engagement, improved teaching capacity through local training initiatives, and the effective use of digital tools like WhatsApp and YouTube to support religious learning. Dialogical spaces were also created to foster social cohesion. Conclusion: Religious literacy, developed through contextual and dialogical methods, serves not only as knowledge transmission but also as a strategic tool for minority empowerment and cultural preservation. The model offers a replicable framework for other marginalized groups.